Oral Health Hygiene Status And Factors Related To Oral Health Of Soldiers Of Bangladesh Army Attended Mobile Dressing Station (MDS), Khagrachari Cantonment - Haque, Md Anwarul; Rahman, Ashiqur; Akter, Mst Ralifa; Afroz, Rumana (Bangladesh Armed Forces Medical Journal, 2024)
Background: Oral health is the state of the mouth, oral cavity, teeth and oro-facial structures that enables individuals to perform essential functions like eating, breathing and speaking, and encompasses psychosocial dimensions such as self-confidence, well-being and the ability to work without pain, discomfort and embarrassment. The aim of this study was to asses oral health hygiene status and to bring into focus the factors related to oral health of the soldiers serving in Bangladesh Army and also to find out the factors related to behavior, the oral health status and socio demographic status among them. Methods: A cross-sectional study was conducted among 108 purposively selected soldiers of Bangladesh Army who attended Mobile Dressing Station (MDS), Khagrachari Cantonment during the period of August to September 2022. Data were collected by face to face interview using a semi-structured questionnaire and by check list reviewing medical documents. Results: The Mean (±SD) age of the participants was 32.50(±2.08) years and ages of them were between 20-45 years. Among the participants, 78.70% were married, 54.62% and 45.38% were SSC and HSC qualified respectively. Maximum participants (76%) used to brush their teeth in the morning. 86% participants used tooth paste and 11.12% participants used tooth powder as cleaning materials. Usually 48% visited dental clinic for gum bleeding. 71% of the participants had no bad habits of affecting the oral health except 15% were with a habit of smoking. Among 46% participants with abnormal gingival colour, had the habit of taking gul (6.9%), some participants (9.35%) with the habit of smoking were found with bleeding gum. A remarkable number of respondents (6.24%) with gum swelling had the habit of taking gul. Among all, 44% of the participants had swelling of gum. 43% of participants had abnormal gingival colour and 5% had gingival ulceration. Conclusion: Lack of personal and oral health awareness among the soldiers lead to various types of oral disease which needs to exhilarate for a healthy life. Bangladesh Armed Forces Med J Vol 56 No (1) June 2023, pp 14-20